(untitled) (Ustozlar uchun, 2025)
The English Civil War (1642–1651) had a profound influence on English literature, shaping its moral and political consciousness. During this turbulent period, writers like John Milton and John Bunyan used literature as a means of spiritual and ideological expression. Milton’s works, such as Areopagitica and Paradise Lost, emphasized freedom, divine justice, and human responsibility, while Bunyan’s The Pilgrim’s Progress reflected the moral strength and faith of ordinary believers. Both authors transformed personal and national struggles into timeless literary creations that defined English thought and identity. Their works demonstrate that literature can serve as a weapon of truth, faith, and reform even amid war and oppression.